(untitled) (Discourse of Law and Administration, 2025)
Rapidly developing teleinformatics technology is widely used by the National Fiscal Administration to obtain and process information about taxpayers. The legislator does not always keep up with the dynamic development of telecommunication tools with the regulations guaranteeing the protection of taxpayers’ rights. In a decidedly pro-fiscal administration, this may lead to abuse on its part. In a situation where the possibility of conducting analytical, forecasting and research activities concerning phenomena remaining within the competence of the National Fiscal Administration and conducting risk analysis, profiling and decision-making in an automated manner is legally sanctioned, special attention should be paid to guarantees of the procedural rights of taxpayers and controlled entities. The subject of this study is to present teleinformatics tools used to conduct automated activities by the National Fiscal Administration in relation to the procedural guarantees resulting from the Tax Ordinance and the Act on the National Fiscal Administration.